Pengaruh Citra Merek Dan Harga Terhadap Keputusan Pembelian Pada E-Commerce Shopee: (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Bandar Lampung) - Hatta Pinasthika, Al Shifa; Alam, Iskandar Ali (Politeknik Negeri Ambon, 2023)
This research was conducted to analyze the effect of brand image and price on the purchasing decisions of Shopee Indonesia customers. This type of research is quantitative. The number of samples in this study amounted to 107 respondents with a non-probability sampling technique with a purposive sampling approach. Data collection was carried out by distributing questionnaires that had been tested for validity and reliability. Respondents in this study were students of management class 20 at the University of Bandar Lampung. This research uses multiple linear regression analysis. The research results show that brand image has a significant influence on purchasing decisions, then price has a significant influence on purchasing decisions, and brand image and price together have a significant influence on purchasing decisions. Â Keywords: Brand Image; Price; Purchase Decision